Design principles and biological applications of red-emissive two-photon carbon dots - Pooria Lesani (Nature Portfolio, 2021)
Carbon dots are suitable for a range of biological applications due to their unique physicochemical properties and biological behavior. This Review summarizes research related to the emerging field of red-emissive two-photon carbon dots for bioimaging, biosensing, and phototherapeutic applications.